A Review on the Nadi Vikriti w.s.r to Pranavaha Strotas - Gusain, Tanvi; Suhail, Amir (International Research Journal of Ayurveda & Yoga, 2022)
Treatment in Ayurveda is not all similar as the modern medicine. Ayurveda is based on various siddhanta’s such as tridosha, panchamahabhoota, sapta dhatu, dashvidha parikshya bhava to name a few. The prognosis of a patient or the severity of a disease cannot be decided by a single thing. We use rogi-rog pareeksha to identify diseases. Dashvidh pareeksha is used to evaluate the patient, whereas panch-nidan pareeksha is used to diagnose the ailment. To determine a disease’s cause, a questionnaire must be created. By simply sensing the radial artery’s or any other pulsating artery’s pulse, this diagnosis can be made with the use of nadi vigyan. Hrudya, mahastrotas & rasvahai dhamniya forms the moola of pranavaha strotas (Channels carrying vital life element). As the name indicates prana is something in which the life flows. In other words, pranavaha strotas play an important role in maintaining life energy, if not it can lead to death. So, it is important to know nadi vikriti which arises due to the physiological disturbances in the pranavaha strotas.in this paper we will review on the nadi vikriti with special reference to diseases related to pranavaha strotas, which can be achieved through appropriated knowledge and practice of its nadi pareeksha (Pulse diagnosis).